The handbook of language emergence - MacWhinney, Brian; O'Grady, William (Hoboken : Wiley-Blackwell, 2015)
'This book explores the latest integrated theory for understanding human language. The authors focus on the ways in which the learning, processing, and structure of language emerge from a competing set of cognitive, communicative, and biological constraints. In addition, the book examine forces on widely divergent time scales, from instantaneous neurolinguistic processing to historical changes and language evolution. Key theoretical, empirical, and methodological issues are also addressed'--
Machine generated contents note: Notes on Contributors Introduction I. Basic Language Structures: 1. The Emergence of Phonological Representation Patricia Donegan 2. Capturing Gradience, Continuous Change, and Quasi-Regularity in Sound, Word, Phrase, and Meaning Jay McClelland 3. The Emergence of Language Comprehension Maryellen McDonald 4. Anaphora and the Case for Emergentism William O'Grady 5. Morphological Emergence Peter Racz, Janet Pierre-Humbert, Jennifer Hay, & Viktoria Papp 6. Metaphor and Emergentism Zoltan Kovecses 7. Usage-based Language Learning Nick Ellis, Matthew O'Donnell, & Ute Romer II. Language Change and Typology 8. Emergence at the Crosslinguistic Level: Attractor Dynamics in Language Change Joan Bybee and Clayton Beckner 9. The Diachronic Genesis of Synchronic Syntax Tom Givon 10. Typological Variation and Efficient Processing John Hawkins 11. Word meanings across languages support efficient communication Terry Regier, Charles Kemp, and Paul Kay III. Interactional Structures 12. Linguistic Emergence on the Ground -- a Variationist Paradigm Shana Poplack and Rena Torres Cacoullos 13. The Emergence of Sociophonetic Structure Paul Foulkes and Jennifer Hay 14. An Emergentist Approach to Grammar Paul Hopper 15. Common Ground Eve Clark 16. The Role of Culture in the Emergence of Language Dan Everett IV. Language Learning 17. Learnability Alexander Clark 18. Perceptual Development and Statistical Learning Erik Thiessen and Lucy Erickson 19. Language Emergence in Development -- A Computational Perspective Stewart McCauley, Padraic Monaghan, & Morten Christiansen 20. Perception and Production in Phonological Development Marilyn Vihman 21. The Emergence of Gestures Jordan Zlatev 22. A Constructivist Account of Child Language Acquisition Ben Ambridge & Elena Lieven 23. Bilingualism as a Dynamic Process Ping Li 24. Dynamic Systems and Language Development Paul van Geert and Marjolijn Verspoor V. Language and the Brain 25. Models of Language Production in Aphasia Gary Dell & Nathaniel Anderson 26. Formulaic Language in an Emergentist Framework Diana Van Lanckner Sidtis 27. Language Evolution -- An Emergentist Perspective Michael Arbib.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Language and languages -- Origin; Linguistics; Electronic books